Analsisis pemasaran dan keuangan digital terhadap daya saing global hasil pertanian komoditas ekspor di provinsi Sulawesi-Selatan - Arya, Muhammad Irfan; Djufri, Farhan; Beddu, Hartina (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Digital marketing is a marketing strategy using digital media and the internet. The concept and application of digital marketing is something that is done to boost product sales from a brand. Digital marketing really helps business actors to attract domestic and international consumers and potential consumers quickly. The acceptance of technology and the internet in society is very widespread so it is not surprising that digital marketing activities are the main choice for business people. As a result, business actors compete with each other to create interesting content to display in their marketing in cyberspace. Financial technology is one of the factors that supports the increase in agricultural commodities that have global competitiveness. The presence of financial technology has had a big influence on consumer behavior because of the convenience it offers which includes payment methods, fund transfers, fund collection, fund loans, and asset management which can be done and processed in a short time. It is not surprising that fintech ultimately influences people's lifestyles, including society. The objectives of this research are: (1) to analyze the influence of digital marketing on competitiveness, (2) to analyze the influence of digital finance on competitiveness. (3) to analyze the simultaneous influence of digital marketing and digital finance on competitiveness. Research locations in Luwu, East Luwu, Enrekang, North Toraja and Bone Regencies. The sample size was 400 farmers. Data collection method through questionnaire data. The sampling method is simple random sampling and the analysis method uses regression  analysis. The research results show that: (1) Digital marketing has a positive and significant effect on competitiveness. (2) Financial technology has a positive and significant effect on competitiveness. (3) Digital marketing and financial technology simultaneously have a positive and significant effect on competitiveness.